Microbiological Evaluation of Foods for Special Medical Purposes of Children - Pınar Mursalıoğlu Kaynar; Elçin Günaydın (Turkish Journal of Agriculture: Food Science and Technology)
Foods for special medical purposes are specially produced or formulated with the intention of regulating children's diets for specific nutrition applications, and used under medical surveillance. These food should not offer a microbiological risk to human health as well as their compositions. The purpose of this study was the microbiological evaluation of foods for special medical purposes used in children’s diet. For this evaluation, eleven imported foods for special medical purposes that were sold in Ankara-Turkey were analyzed in terms of Salmonella spp., coagulase positive staphylococci, staphylococcal enterotoxin, Escherichia coli, Escherichia coli O157, Enterobacteriaceae, Listeria monocytogenes, and Bacillus cereus. The bacterial examinations were done according to each related EN ISO standart methods. In result of the examination, the microbial growth was not observed on the food samples. In conclusion, the samples investigated have no microbiological risk. Also, consumers should examine their expiration dates during purchase because the expiration dates declared on the foods have showed their microbiological stability.